Improving the Quality of Reading and Writing the Qur'an in Sukawera Village, Kertasemaya District, Indramayu Regency - Shulistia (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to determine the improvement in the quality of reading the Qur'an in Sukawera Village, Kertasemaya District, Indramayu Regency. The Qur'an as a guide and the first and main guide for mankind has laid the foundations of the straight path, then ordered humans to walk towards Him. When someone reaches the stage of awareness that the Qur'an contains various explanations of various issues, summarizing many truths in it, then at that time he will realize how great the benefits are in studying it. The purpose of religious learning activities for children is to get to know religion and improve the ability to read and write the Qur'an and memorize it for children in Sukawera Village. The approach used in implementing this supporting program is to conduct direct dialogue conducted by the interviewer and observe the atmosphere by conducting a general exploration thoroughly. The analysis used by systematically searching and arranging notes from observations, interviews, pre-test and post-test results to improve the researcher's understanding of the case being studied. The results of this activity are an increase in the ability to read the Qur'an and memorize it correctly according to tajwid.